Constructs of depression and distress in diabetes: time for an appraisal. Issue 6 (June 2015) - Snoek, Frank J; Bremmer, Marijke A; Hermanns, Norbert
Summary: Depression presents in roughly 20% of people with diabetes worldwide, and adversely affects quality of life and treatment outcomes. The causes of depression in diabetes are poorly understood, but research suggests a bi-directional association, at least for type 2 diabetes. Inconsistent findings regarding prevalence and depression treatment outcomes in patients with diabetes seem partly attributable to inconsistencies in the definition and measurement of depression and in distinguishing it from diabetes-distress, a psychological concept related to depression. We review evidence suggesting that diabetes-distress and depression are correlated and overlapping constructs, but are not interchangeable. Importantly, diabetes-distress seems to mediate the association between depression and glycaemic control. We propose a model to explain the direct and indirect effects of depression and diabetes-distress on glycaemic control. Additionally, using emerging insights from data-driven approaches, we suggest three distinct symptom profiles to define depression in patients with diabetes that could help explain differential associations between depression and metabolic abnormalities, and to tailor interventions for depression. Future research should focus on further refining depression profiles in patients with diabetes, taking into account the natural history of diabetes and depression, clinical characteristics, and diabetes-distress. The assessment of diabetes-distress and depression in research and clinical practice will be essential to identify high-risk patients with different mental health needs.